Electronic Customer Relationship Management (E-CRM) System for Jordanian Ministry of Higher Education (MOHE) to Address & Decrease the Rate of Unemployed Jordanian Graduates - Kanaan, Anas Ghassan J. (2012)
Globally the way of getting information and sharing it on internet is getting easy through using the Web-based systems as an effective tool to do such services. So with the existence of such tools (Web-based systems) are used as a medium by many organizations across the internet to integrate with other institutions. As well, the web-based systems are not only used as information distribution for business activities, education purposes, but also it plays a major role for the administration of trade, student admission systems, integrity and maybe also security in various companies. The system that is related to the section of Customer Relationship Management (CRM) is a system, its main concern on the customer satisfaction and builds its future work and reputation according to that. As the progression of the project it includes the problem that we are facing and the limitation that will be encountered through the design of this project. Now Employment companies and Offices are working manually in Jordan. So we have to make an important goal to fulfill in order to have a more accurate system in place to gain and manage the requirements of the business and the service for the customers, to get the number of the unhappy customers decreasing and proving that this way is more effective and affective along the large numbers of unhappy customers, while it is so hard to get every customer pleased but Web-based Systems can be easy to manage the quality control as an online supported tool. Making the web-based customer support system a well organized and well maintained system and by that it can be called an Electronic Customer Relationship Management System (ECRM) and its crucial for any online survey, it can be reached by related institutions, anytime, anywhere that can add values to the users. Thus, this study proposed a web based system to address and decrease the rate of unemployed Jordanian Graduates. This web based has been developed using Java programming language & C# to create web pages, SQL to create, store, and retrieve the data.